2004
DOI: 10.1007/s00436-004-1081-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diethylcarbamazine on the ultrastructure of microfilariae of Wuchereria bancrofti in vivo and in vitro

Abstract: An ultrastructural study of microfilariae of Wuchereria bancrofti was performed after treatment in vitro and in vivo with diethylcarbamazine citrate (DEC). The morphological alterations produced by treatment in vitro with 5 micro g/ml of DEC were the loss of microfilarial sheaths and lysis of the cytoplasm, with the destruction of all organelles and the formation of several vacuoles, the contents of which presented various degrees of electron-density, or showed an empty appearance. Some of these vacuoles seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…DEC severely affected microfilariae cells inducing extreme cellular disorganization with abundance of degenerating organelles, large and numerous vacuoles, and nuclear condensation Florêncio and Peixoto 2003;Peixoto et al 2004). Interestingly, although the cellular content in some cells have disappeared, the plasma membrane maintained its integrity .…”
Section: Introductionmentioning
confidence: 99%
“…DEC severely affected microfilariae cells inducing extreme cellular disorganization with abundance of degenerating organelles, large and numerous vacuoles, and nuclear condensation Florêncio and Peixoto 2003;Peixoto et al 2004). Interestingly, although the cellular content in some cells have disappeared, the plasma membrane maintained its integrity .…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of reactive oxygen species observed after DEC treatment were due to >80% killing of circulating microfilariae resulting in excessive release of parasite products and Wolbachia-associated molecules and leading to high oxidative stress. Although McGarry et al (2005) reported that iNOS and COX1 mediate mf killing by DEC in vivo in mice intravenously injected with mf, another study has also reported the direct activity of DEC against W. bancrofti microfilariae that results in exsheathment, organelle damage and cytolysis (Peixoto et al 2004), which occur both in vitro and in vivo. Those findings suggest that DEC may have a direct effect on worms beyond its interaction with host-derived pathways as reported here.…”
Section: Discussionmentioning
confidence: 96%
“…Bestrahlung mit Gammastrahlen bis 10,5 Gy (Gray) tötet Mikrofilarien von Wuchereria bancrofti nicht ab [84]. Behandlung mit 5mg/ml Diehtylcarbamazin in vitro löste Mikrofilarien von Wuchereria bacrofti auf [85], Behandlung mit 2 bis 10 µM Mefloquine (Lariam® zur MalariaProphylaxe) tötete Mikrofilarien von Brugia malayi nach 10 h bis 3 Tagen ab [86].…”
Section: Möglichkeiten Der Abtrennung Und Inaktivierung Von Infektionunclassified